The faces of local TV news in America: youth, whiteness, and gender disparities in station publicity photos. Issue 3 (4th May 2018) - Bock, Mary Angela; Cueva Chacón, Lourdes Miriam; Jung, Hyeri; Sturm, Heloisa Aruth; Figueroa, Ever J.
Abstract: TV news is a visual medium that requires its on-air journalists to look good, but a history of lawsuits and survey research suggests that this burden is spread unevenly. Critics charge that women are expected to look younger and sexier, and minority broadcasters are held to a White standard of beauty. This project investigated the reality behind those complaints by examining the faces of on-air journalists working for local stations in the US according to race, gender, and attractiveness. The resulting content analysis of more than 400 online publicity photos suggests that a certain look dominates for men and for women and that the range of appearance standards is wider for men than women.